"Capac Ñan" Stairway Fashion Hemilaminectomy: A New Minimally Invasive Multilevel Option to Treatment of Cervical Stenosis. A Study with 24 Months of Follow-Up. Issue 1 (April 2016) - Pesantez, Carlos Fernando Arias
Introduction: There are many options to decompress the cervical spine on posterior way in multilevel disease, however the muscular injury and instrumentation is a big problem in traditional surgery, the minimally invasive procedures can achieve optimal decompression without muscle injury, preserving the posterior ligamentous tension band with less pain, bleeding and hospitalization, providing improvement in short time. Materials And Methods: We present an study with 15 patients with symptoms of multilevel cervical stenosis and MRI shows multilevel stenosis too, All the patients underwent minimally invasive uniportal multilevel decompression. We use VAS, Neck Disability index and Nurick clinical scale with follow up of 24 months. We made POP early (2 weeks) MRI and dynamics rx. Results: The Vas preop was mean 9 and 2 on 24 monts. Neck Disability index was 20 preop and 10 POP 24 months. The Nurick clinical scale shows improvement of one time line. The surgical time was mean 22 minute(mean) each level, blood lose 11cc (mean) each level, hospital discharge on 23 hours after surgery and return to daily activities mean 10 days. Conclusions: The "Capac Ñan" starway fashion minimally invasive hemilaminectomy procedure can be safe and efective to decompress a cervical spinal cord on multilevel disease without instability, muscular injury and let a better time to recovery and return to daily activities. We need more experience to make a final conclusions.